Effect of Camphor Incorporation on the Material and Antibacterial Properties of Soy Protein Isolate Films - Rani, Priya; Kumari, Chandrakanti; Kumar, K. Dinesh; Kumar, Rakesh (Journal of Research Updates in Polymer Science, 2023)
Seeking for green alternatives to synthetic plastics, soy protein based plastics are becoming quite a popular choice. Soy protein isolate (SPI) is a plant derived protein that holds fair film forming abilities. It demonstrates evenness of film surface, decent tensile strength and interacts easily with a wide range of additives. Additives are generally added to improve the material properties and antibacterial nature of the film. In this study, we have explored the effect of camphor incorporation on the material properties and overall performance of the film. SPI based films (having 7% SPI (w/v)) were prepared by solution casting method. The concentration of camphor was varied from 0.5 to 3% w/w of 7% SPI. The films prepared by camphor addition were characterized for their transmittance, Fourier Transform Infrared (FTIR) spectroscopy and mechanical properties. The FTIR spectra confirm the incorporation of camphor as a major change in the band intensity was seen compared to neat films. However, camphor addition made the films hydrophilic and a noticeable decrease in the tensile strength was seen. The water vapour transmission rate increased upon camphor addition as compared to neat SPI films. Nevertheless, camphor- SPI film was stable as very minimum leaching occurred during the study. Unlike the neat camphor solution (1-3% w/v), the camphor modified SPI films didn’t exhibit antibacterial activity against Listeria monocytogenes and Escherichia coli. Camphor was seen to significantly increase the antioxidant properties of SPI films.